Pengaruh Pengungkapan Emisi Karbon dan Kinerja Lingkungan terhadap Nilai Perusahaan: Studi Empiris Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia 2018-2022 - Putri, Febby Anjani; Serly, Vanica (Universitas Negeri Padang, 2024)
This study aims to examine carbon emissions and environmental performance against the value of companies in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. This research is quantitative research. Sampling techniques using targeted sampling. The number of samples during the study year totalled 140 data. The statistical method used is multiple linear regression analysis. The results show that carbon emissions have a significant negative effect on the value of the company while environmental performance has a significant effect on the value of companies in mining companies in 2018-2022.